Mapping Financial Sector Vulnerability in a Non-Crisis Country - Otker, Inci (IMF Policy Discussion Papers; Policy Discussion Paper, 1999)
The forward-looking framework expounded in this paper links a qualitative evaluation of system-wide vulnerability (covering macro, sectoral, institutional, and systemic liquidity issues) with a quantitative assessment of the financial condition of significant financial institutions. Based on vulnerability criteria and judgmental stress tests, twelve indicators of soundness (measuring risk exposure, solvency, liquidity, profitability, and supervisory assessment) are developed. This holistic methodology can be used not only as an early warning/crisis-avoidance system to identify potential systemic problems-and problem institutions-requiring immediate attention, but also to pinpoint needed reforms in the legal, regulatory, and institutional infrastructure that can lessen the likelihood of a future crisis.